The mosque of the Two Qiblahs in Madinah - Omer, Spahic (www.islamicity.org, 2019)
This is an important historical mosque. It is one of the earliest mosques in Islam. It was established during the Prophet’s time for an outlying neighbourhood of Madinah. Its significance lies in the fact that after the Prophet (pbuh) received a commandment to change the qiblah or prayer direction from al-Masjid al-Aqsa in Jerusalem to al-Masjid al-Haram (Ka’bah) in Makkah, the entire congregation led by a companion in this mosque changed direction in prayer. Henceforth the mosque was known as masjid al-qiblatayn (the mosque of the two qiblahs) as both qiblahs were faced in a single prayer.